The exposome : a primer : the ex-POZE-ohm : a pr i m'-er : the environmental equivalent of the genome - Miller, Gary W. (Professor of environmental health) (Amsterdam : Elsevier/Academic Press, 2014)
Suitable for both students and scientists in disciplines including toxicology, environmental health, epidemiology, and public health, this book details the purpose and scope of this field of study, its practical applications and how it complements a broad range of disciplines
1. The exposome: purpose, definition, and scope2. When the genome falls short: limitations of a gene-centric view of health3. Omic-based technologies and their impact on the exposome4. The exposome in environmental health sciences and related disciplines5. Managing and integrating exposome data: maps, models, computation, and systems biology6. An exposome education: university and community-the practical exposome7. Staging the exposome: a vision for international collaboration
Includes bibliography
Keywords: Environmentally induced diseases; Environmentally induced diseases -- Epidemiology; Environmental health